The role of oxidative stress in ovarian aging: a review - Fei Yan; Qi Zhao; Ying Li; Zhibo Zheng; Xinliang Kong; Chang Shu; Yanfeng Liu; Yun Shi (BMC, 2022)
Abstract Ovarian aging refers to the process by which ovarian function declines until eventual failure. The pathogenesis of ovarian aging is complex and diverse; oxidative stress (OS) is considered to be a key factor. This review focuses on the fact that OS status accelerates the ovarian aging process by promoting apoptosis, inflammation, mitochondrial damage, telomere shortening and biomacromolecular damage. Current evidence suggests that aging, smoking, high-sugar diets, pressure, superovulation, chemotherapeutic agents and industrial pollutants can be factors that accelerate ovarian aging by exacerbating OS status. In addition, we review the role of nuclear factor E2-related factor 2 (Nrf2), Sirtuin (Sirt), mitogen-activated protein kinase (MAPK), protein kinase B (AKT), Forkhead box O (FoxO) and Klotho signaling pathways during the process of ovarian aging. We also explore the role of antioxidant therapies such as melatonin, vitamins, stem cell therapies, antioxidant monomers and Traditional Chinese Medicine (TCM), and investigate the roles of these supplements with respect to the reduction of OS and the improvement of ovarian function. This review provides a rationale for antioxidant therapy to improve ovarian aging.